Duality theory and cost function analysis in a regional context: the impact of public infrastructure capital in the Greek Regions - Antonis Rovolis; Nigel Spence (European Regional Science Association (ERSA), 1998)
There has been a significant resurgence of interest in the effects of public capital on the economic fortunes of the private sector of late. This renewed concern was sparked by the research of Aschauer on US infrastructure and the ensuing debate between himself, Munnell and Holtz-Eakin. This debate and much of the subsequent work in the US and elsewhere has been conducted utilising production functions. There is, however, another potentially more rewarding strand in the infrastructure literature that is based on duality theory and cost function analysis. This approach has been thought of as overcoming some of the methodological problems inherent in the use of production functions in this research context. This paper, using cost functions, attempts to estimate the impact of the productive categories of the Public Investment Programme of Greece on regional development, and especially on large scale manufacturing activities. The results demonstrate that public capital has a significant positive impact on the performance of the private sector, and reduces private costs of production. Also considered here are the links between infrastructure provision and private sector input factors of production.
Keywords: 330